A Concise Introduction to Greek Environmental History: Research Hubs, Threads, Themes and Projections into the Future - Vlachos, George L. (The Historical Review/La Revue Historique, 2023)
This article aims to provide a brief overview of the institutional emergence and development of environmental history in Greece, starting from its humble beginnings during the latter part of the 2000s to the rapid flourishing of the field in the late 2010s. After a brief discussion of the emergence of environmental history internationally, it highlights how environmental history evolved from an extracurricular research interest of a few scholars into a discipline that is being fostered by many institutions and has already appeared in several university curricula. Additionally, the article provides a coherent list of works by Greek scholars that have contributed to the development of environmental history in Greece. The last part of the article acts as a prologue to this special section, summarising the main idea behind each article and the elements that make them fit together, underlining the reason why it focuses on the concept of conflict and its environmental repercussions.